Understanding global conflict & cooperation intro to theory & history - Nye, Joseph S. (Pearson, 2014)
This text deftly employs lessons from both theory and history to evaluate conflict and cooperation among global actors and to provide students with a resilient analytical framework. From twentieth and twenty-first century conflicts to global trade and finance, global governance, and the information revolution, Understanding Global Conflict and Cooperation, formerly known as Understanding International Conflicts, expands substantially on previous editions of this classic work to provide a lucid and thought-provoking survey of international relations today.